Deconstructing Stigma and Agency of Female Sex Workers in Gangubai Kathiawadi : A Derridean Perspective - Saragih, Evi Irawanti (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study examines the deconstruction of stigma and agency of female sex workers in Gangubai Kathiawadi through Jacques Derrida’s deconstructive framework. Popular cinema often positions female sex workers within hierarchical moral binaries particularly moral/immoral that limit subjectivity and agency. Using a qualitative descriptive-analytical method, this research analyses key scenes, dialogues, and visual elements as discursive formations that construct and regulate meaning. The analysis shows that while the film reproduces stigma through moral discourses that normalize subordination and encourage internalized labelling, it also destabilizes these hierarchies by revealing narrative contradictions and moral hypocrisy. These tensions expose the structural reliance of social and political institutions on marginalized communities. Furthermore, the film reconstructs agency not as radical liberation, but as a gradual, relational, and strategic process involving critical awareness, counter-discourse, institutional negotiation, and advocacy for educational rights. Ultimately, agency is depicted as a context-bound socio-political practice operating within structural constraints, reframing marginalized women as political subjects capable of negotiating power and reconfiguring dominant discourses.